Accident Causation Theories and Tax Implication to Road Traffic Accidents in Nepal - Mishra, A. K.; Niraula, Subhash (Intellectual Journal of Academic Research, 2024)
This editorial is to highlight how accident theories can provide insights into the contributing factors to accidents and inform the development of targeted interventions and comprehensive safety strategies and tax implication. The article discusses several accident causation theories, including Domino Theory, Human Factors Theory, Accident/Incident Theory, Epidemiological Theory, Systems Theory, Energy Release Theory, and Combination Theory. Each theory is analyzed in the context of Nepal's transportation sector, with an emphasis on their relevance to the unique challenges faced in the country. Additionally, the editorial incorporates insights from social media, which garnered substantial community engagement and responses. The analysis reveals that heavy taxation on vehicles in Nepal significantly contributes to road and aviation accidents by creating a financial burden on vehicle owners. This burden deters regular maintenance, compels reliance on emergency repairs, and shifts focus from safety to productivity, ultimately increasing accident risks. The editorial argues for the necessity of reducing taxes to alleviate this burden, thereby encouraging regular maintenance and enhancing safety measures through maintenance insurance. The editorial emphasizes the need for policy reforms aimed at reducing vehicle taxes and improving public transport reliability to ensure a safer environment for all road users. It underscores the importance of addressing the financial aspects of vehicle ownership in conjunction with safety measures to reduce accident rates effectively.